Nie mogą czy nie potrafią? Analiza zaangażowania służb społecznych w procesy rewitalizacji = Not allowed to or not able to? Analysis of the engagement of social services in revitalization processes - Frątczak-Müller, Joanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article analyzes the engagement of social services in the planning and implementation of revitalization processes. Of particular interest here are the applicable rules of process socialization and their effects for the social life practice. A weak engagement of residents in revitalization areas raises questions about the scale and rules of cooperation between social workers and representatives of local governments in diagnosing, setting revitalization goals and tasks, and implementing tasks assigned to them.
Keywords: służby społeczne; rewitalizacja; programowanie strategiczne; partycypacja społeczna; proces uspołecznienia; social services; revitalization; strategic programming; social participation; socialization process